Metal-based nanoparticles: Promising tools for the management of cardiovascular diseases - Nour K., Younis (2021)
Cardiovascular disease (CVD) is the leading cause of death worldwide. A search for more effective treatments of CVD is increasingly needed. Major advances in nanotechnology opened new avenues in CVD therapeutics. Owing to their special properties, iron oxide, gold and silver nanoparticles (NPs) could exert various effects in the management and treatment of CVD. The role of iron oxide NPs in the detection and identification of atherosclerotic plaques is receiving increased attention. Moreover, these NPs enhance targeted stem cell delivery, thereby potentiating the regenerative capacity at the injured sites. In addition to their antioxidative and antihypertrophic capacities, gold NPs have also been shown to be useful in the identification of plaques and recognition of inflammatory markers. Contrary to first reports suggestive of their cardio-vasculoprotective role, silver NPs now appear to exert negative effects on the cardiovascular system. Indeed, these NPs appear to negatively modulate inflammation and cholesterol uptake, both of which exacerbate atherosclerosis. Moreover, silver NPs may precipitate bradycardia, conduction block and sudden cardiac death. In this review, we dissect the cellular responses and toxicity profiles of these NPs from various perspectives including cellular and molecular ones.